The 'Dark Side' of Psychological Ownership during Times of Change. Issue 4 (2nd October 2019) - Cocieru, Ovidiu C.; Lyle, Matthew C. B.; Hindman, Lauren C.; McDonald, Mark A.
ABSTRACT: Scholars have suggested that psychological ownership can have a 'dark side' in organizational contexts but have yet to fully explore its negative outcomes. In this paper, we argue that when an employee feels psychological ownership toward a project, and an organizational representative imposes subtractive and revolutionary changes on that project, it is likely for the employee to experience negative emotions, reduced affective commitment to change, and intentions to resist change. We further suggest that several factors will moderate the relationship between psychological ownership and negative reactions to change, namely change recipient narcissism and need for control, the importance of the project in the recipient's self-definition, and transformational leadership displayed by the change initiator. We thus argue that psychological ownership can have a 'double-edged sword' effect in organizations, as feelings of ownership can bring many positive outcomes in stable environments but might also lead to several negative effects in times of change. We close with a discussion of the theoretical implications this work has for scholarship on organizational change and psychological ownership, alongside its practical implications for managers in organizations.